HUBUNGAN POLA MAKAN DENGAN RESIKO KANKER PAYUDARA (Studi Kasus pada Rumah Sakit dan Klinik Onkologi di Banda Aceh) - Eva Fitriyaningsih; Nurliana Nurliana; Ummu Balqis (Pascasarjana Universitas Negeri Medan, 2014)
Abstract The research was aim to investigate the relation between food animal origin dietary patterns and breast cancer in Banda Aceh. This case-control study compared the dietary pattern of food animal origin between 45 breast cancer patients and 45 age-matched controls. Six dietary patterns were difined by food frequency questioner (FFQ): food animal origin, preserved of food animal origin, processing of food, fats and oils, vegetables and fruits patterns. Preserved of food animal origin were significantly associated with the incidence of breast cancer with an odds ratio (OR) 5.86 [95% confidence interval (CI) = 1.49-21.65] respectively; p = 0.013; while food animal origin, processing of food. fats and oils, vegetables and fruits dietary patterns were not associated with the incidence of breast cancer. The conclution of the research that salt fish and keumamah play an important role of the assosiation.Keywords : Breast cancer, dietary patterns, food animal origin